if sec theta+tan theta+1= 0,then find sec theta -tan theta

sec theta + tan theta +1 =0
sec theta + tan theta = -1 ..............(1)
we know that sec2 - tan 2 = 1
therfore   (sec+tan)(sec-tan) = 1
                   -1(sec-tan) = 1..........(from 1)
                       sec-tan=1/-1
         therefore sec-tan=-1
Hope it helps.......Cheers!!!

 
  • 17
SAME AS ARSHAD......IT IS ACTUALLY HELPFULL    
  • -9
Kindly refer to this picture for the solution👇👇.Hope it is helpful to you.😀😀

  • 8
Here's your answer

  • -2
answer is -1 
 
  • 0
What are you looking for?